Una proposta per Mazzolino giovane: il San Rocco della Pinacoteca Nazionale di Ferrara - Valentina Lapierre (Annali Online dell'Università di Ferrara. Sezione Lettere)
The attribution proposed in this paper attempts to add a new piece to the reconstruction of the early production of the Ferrarese painter Ludovico Mazzolino (circa 1480 – circa 1528/1530), often coincident with the commission of works intended for public fruition, usually of a large format.